A rejoinder to the reply of the Superior of the Society of the Sisters of Mercy of Devonport and Plymouth, to a pamphlet entitled Miss Sellon and the "Sisters of Mercy" (Thomas Hatchard [etc.], 1852)
The same is James Spurrell.